An Unusual Amyloid Goiter in a 48-Year-Old Woman with Rheumatoid Arthritis, Secondary Amyloidosis and Renal Failure - B. López-Muñoz; L. Greco Bermúdez; D. Marín-Jiménez; M. F. Sánchez de la Fuente; A. Franca Capparelli; I. Mascarell Martínez; S. Serrano Corredor (Case Reports in Endocrinology)
Amyloid goiter (AG) is characterized by the presence of deposits of amyloid protein in the thyroid tissue in sufficient amounts to produce enlargement of the gland, accompanied by fat deposition or thyrolipomatosis. It can be seen in long-standing inflammatory disorders, with the common characteristic of amyloidotic renal failure. In daily practice, practitioners should pay attention to the differential diagnosis in patients with suggestive co-morbidities for amyloidosis. The clinic is a progressive increase of the thyroid gland with compressive symptomatology (dyspnea, dysphagia, and changes in the voice). The main imaging finding is diffuse fatty infiltration of the thyroid. The amyloid goitre was most probably in the general context of amyloidosis, regardless of the other complications. We present a case of a 48-years-old female with amyloid goiter secondary to rheumatoid arthritis and renal failure.